Crimes culturalmente motivados: cultural defense nos casos de violência sexual contra a mulher - Rodrigo Iennaco de Moraes (2017)
Globalization and the growing of populational migratory flows redeemed the debates over the cultural notes of law. In this context the debate over multiculturalism and its limitations on matters of human rights as a juridical cathegory that aims at universality has broken out. In this thesis, criminal law is regarded as national law, but marked lack of cultural neutrality (cultural non-neutrality). In face of these paremeters and in light of feminism as an ethical argument, consequences of cultural pluralism and right to diversity are studied under the framework of general theory of crime, pointing out to the rescue of the culturalist conception of criminal wrongfulness, in material terms. The understanding of sexual violence against women takes root in psychological and social dualism, setting itself as a human behavior related to sexual orientation, and, at the same time, subject to symbolic appropriation at the level of private customs and political connotations. Criminal law then has limited influence on the management of conflicts of this sort, although it must act as ultima ratio limiting expression from the perspective of the promotion of guaranties of freedom and dignity of vulnerable victims. Thus, the greater the severity of th offense and the more intense the use of violence, the less the relevance of the cultural factor underlying the behaviour of the agressor. Therefore, the criminal wrongfulness in sexual crimes culturally motivated is studied; specifically, it is asked under which limits justificatory juridical effectiveness could be granted to cultural factor in cases of sexual violence against women. For this purpose, as theoretical assumption, the concepts of culture and violence and its appropriation by juridical discourse are reassessed. Brazilian multiculturalism is evaluated as complex, in comparison to other models of discursive systematization exclusively structured upon immigration or the autonomy of indigenous communities. Criminal law, as an expression of hegemonic culture, even if settled onto democratic political bases, cannot rest its judgements in disregard of minoritarian cultural factor. Beyond concepts of neokantion character, this work tries to establish an argumentative programm as hermeneutic route to comprehension of criminal liability in such cases.